Women Entrepreneurship in Bihar: Analysing Behavioural Patterns and Growth Determinants - Kumari, Qurie; Ghosh, Souvik; Rath, Swagat Ranjan (International Journal of Bio-resource and Stress Management, 2025)
The current study examined the entrepreneurial behaviour of female entrepreneurs in Bhagalpur, Bihar, India, from January to May, 2019. Eighty female entrepreneurs from four different business types-goat rearing, dairy farming, stitching, and mushroom cultivation-were polled using an ex-post facto research approach in two randomly chosen blocks. Entrepreneurial behaviour was assessed through seven components: innovativeness, achievement motivation, decision-making ability, risk-taking ability, planning ability, information-seeking behaviour, and self-confidence. Data were collected using an interview schedule and analysed using step-wise multiple regression. The findings revealed that mushroom entrepreneurs exhibited the highest levels of innovativeness, risk-taking ability, and planning ability, whereas dairy farmers scored the lowest in these aspects. Achievement motivation and self-confidence were consistently high across all enterprises. However, information-seeking behaviour was generally low, with heavy reliance on informal sources. Limited access to financial resources, gender norms, and inadequate information-seeking behaviour further constrained their growth. Regression analysis identified economic motivation, family size, age, and use of personal information sources as significant determinants of entrepreneurial behaviour, explaining 66% of its variation. The regression coefficient (0.213) of economic motivation was positively significant, and variables such as age, size of family and use of personal localite information source had a negatively significant relationship with entrepreneurial behaviour. The study concluded that younger entrepreneurs with higher economic motivation and greater exposure to cosmopolite information sources exhibited stronger entrepreneurial behaviour. The findings underscored the need for targeted policies and support mechanisms to foster a more enabling entrepreneurial ecosystem for women in Bihar.